Poder público, saberes médicos e medicina popular no Território do Acre (1904-1930) - Sérgio Roberto Gomes de Souza (Nepan editor, 2015)
This article focusses on the inefficiency of the public health system in Acre, between 1904 and 1930, as emerging from complaints and aid requests written by members of the general public and published in the newspapers of the main cities of the region; and from official documents produced by departmental prefects and governors of the Federal Territory of Acre. The found evidence suggests that the difficulties of access to doctors and medications eventually constituted an important factor in the context of the expansion of other healing methods in the region, with a varied range of social tensions and discursive representations between the social subjects involved in this issue.